HUBUNGAN SELFCARE DENGAN KUALITAS HIDUP PENDERITA DIABETES MELLITUS TIPE 2 DI PUSKESMAS GRIYA ANTAPANI - Daryaman, usan; Aulia, Nissa (Jurnal Sehat Masada, 2025)
Diabetes mellitus is a deadly chronic disease in the world known as the "Mother of Disease" because it triggers a variety of other diseases that can lead to microvascular and macrovascular complications, impacting a decrease in quality of life. Therefore, proper care called self care is needed. Self care is a person's actions to control their health problems including diet management, blood sugar monitoring, drug therapy, foot care and physical activity. The purpose of the study was to determine the relationship between self-care and the quality of life of people with type 2 diabetes mellitus at the Griya Antapani Health Center. The research method uses quantitative descriptive correlation with a cross sectional approach. The sampling technique used purposive sampling with a total of 56 people from a population of 126 people with type 2 diabetes mellitus. The research instrument is in the form of a Summary of Diabetes Self Care (SDSCA) questionnaire to measure self-care and Diabetes Quality of Life(DQOL) to measure quality of life. Data analysis used a spearman rank test with the result of p = 0.001 < 0.05. In conclusion, there is a significant relationship between self-care and the quality of life of people with type 2 diabetes mellitus at the Griya Antapani Health Center. Self-care behaviors that need to be improved are physical activity and regular blood sugar monitoring. It is hoped that people with diabetes mellitus will improve self-care behavior to improve health and prevent further complications of the disease.